2018
DOI: 10.1111/ipd.12455
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effect of previous dental treatment under general anaesthesia on children's dental fear and anxiety

Abstract: Background Dental treatment under general anaesthesia (DGA) is deemed to contribute to children's dental fear and anxiety (DFA), both in the short term and long term. Objective To compare DFA between children who had previous DGA and those who did not. Methods A cross‐sectional survey included 5‐ to 12‐year‐old children who had undergone DGA (n = 43) and a control group who had not (n = 55). Questionnaires were completed by parents regarding sociodemographic and dental profiles. Children's Fear Survey Schedule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…DGA is considered a traumatic treatment for children because of the fear during anesthesia induction ( 39 ). Some clinicians and researchers have reported that children who had experienced DGA have greater dental anxiety than those without a history of DGA ( 40 , 41 ). A recent study by Zhou et al showed that DGA caused a higher risk for dental anxiety when compared with that under physical restraints in the long term, which may lead to uncooperative dental behavior ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…DGA is considered a traumatic treatment for children because of the fear during anesthesia induction ( 39 ). Some clinicians and researchers have reported that children who had experienced DGA have greater dental anxiety than those without a history of DGA ( 40 , 41 ). A recent study by Zhou et al showed that DGA caused a higher risk for dental anxiety when compared with that under physical restraints in the long term, which may lead to uncooperative dental behavior ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since pediatric dental care is a stressful experience for parents, especially when it requires GA [16,18], this study investigated parents' perceptions about DGA for their children. Aldossari et al [19] reported that parents who previously underwent GA described it as a vivid and unpleasant experience. In this current study, most parents showed concerns about DGA.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also reported that dental treatment under GA had a positive psychological impact on treated children [11,12]. Aldossari et al [19] observed that Saudi children who had undergone dental treatment under GA were at a higher risk for dental anxiety even several years after GA. Despite these long-term effects, most parents in our study described that they expected the treatment to eliminate their children's dental pain; hence, they were seemingly unaware of the potential long-term impacts of dental treatment under GA on the quality of life of the treated children.…”
Section: Discussionmentioning
confidence: 99%
“…Som del av oppfølging etter tannbehandling under GA ved IKO, blir omsorgspersonene kontaktet via telefon, fortrinnsvis dagen et- En av indikasjonene for tannbehandling av barn under GA er å få utført nødvendig tannbehandling samt forebygge fremtidig tannbehandlingsvegring-og angst. Dersom barnet forbinder tannbehandlingen med postoperative smerter, kan dette bidra til det motsatte (19). Postoperativ smertelindring er av stor viktighet.…”
Section: Materiale Og Metodeunclassified